Longitudinal motor function in proximal versus distal DMD pathogenic variants. Issue 4 (23rd July 2021) - Thangarajh, Mathula; Bello, Luca; Gordish‐Dressman, Heather; ,
Abstract: Introduction/Aims: There is considerable heterogenicity in clinical outcomes in Duchenne muscular dystrophy (DMD). The aim of this study was to assess whether dystrophin gene (DMD ) pathogenic variant location influences upper or lower extremity motor function outcomes in a large prospective cohort. Methods: We used longitudinal timed and quantitative motor function measurements obtained from 154 boys with DMD over a 10‐y period by the Cooperative International Neuromuscular Research Group Duchenne Natural History Study (CINRG‐DNHS) to understand how the trajectories of motor function differ based on proximal versus distal DMD pathogenic variants. Proximal variants were defined as located proximal to 5′ DMD intron 44, and distal variants as those including nucleotides 3′ DMD including intron 44. Distal DMD variants are predicted to alter the expression of short dystrophin isoforms (Dp140, Dp116, and Dp71). We compared various upper extremity and lower extremity motor function measures in these two groups, after adjusting for total lifetime corticosteroid use. Results: The time to loss‐of‐ambulation and timed motor function measurements of both upper and lower limbs over a 10‐y period were comparable between boys with proximal (n = 53) and distal (n = 101) DMD pathogenic variants. Age had a significant effect on several motor function outcomes. Boys younger than 7 y of age (n = 49) showed gain in function whereas boys 7 y and older (n = 71) declined, regardless of dystrophin pathogenic variant location. Discussion: The longitudinal decline in upper and lower motor function is independent of proximal versus distal location of DMD pathogenic variants.